Researching gender-based violence: embodied and intersectional approaches - Petillo, April D. J.; Hlavka, Heather R. (New York University Press, 2022)
"This book is a interdisciplinary collection of critical, feminist methodological reflections on interpersonal, gender violence that argues for an embodied knowledge and practice in research and academia"--